2002
DOI: 10.17221/5796-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atrazine and zearalenone on the numer of receptor binding sites for 3H-estradiol in the rat uterus cytosol

Abstract: The effect of a daily dose of 14 mg atrazine and/or 2.5 mg zearalenone that were administered to rats during 5 days of estrous cycle on the number of receptor binding sites for 3H-estradiol in uterine cytosol was investigated. Comparison with a control group of animals showed no effect of atrazine influence on the number of receptor binding sites for 3H-estradiol in the rat uterine cytosol until day 6 of the experiment, when a significantly lower value was recorded (P < 0.05). In the group of animals ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, the expression of ERα and ERβ2, which is usually high in carp livers [ 50 ], was found to be reduced after exposing the fish to ZEN. It is known that ZEN competes with natural estrogen for the ER binding sites in the uterus of rats [ 51 ]. However, and in contrast to higher vertebrates, detailed data on the effects of phyto- and mycoestrogens on the expression of the various ER subtypes in fish is lacking and knowledge of endogenous estrogens is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of ERα and ERβ2, which is usually high in carp livers [ 50 ], was found to be reduced after exposing the fish to ZEN. It is known that ZEN competes with natural estrogen for the ER binding sites in the uterus of rats [ 51 ]. However, and in contrast to higher vertebrates, detailed data on the effects of phyto- and mycoestrogens on the expression of the various ER subtypes in fish is lacking and knowledge of endogenous estrogens is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Receptor-binding studies. Molecular studies in pigs, rats, and mice examining mycoestrogen exposure and receptor binding showed binding to ERα and ERβ in the uterus [ 15 , 16 , 17 , 18 ]. Some evidence in rats suggests impacts of ZEN on estrogen receptor density in the uterus as well [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The estrogenic potency of mycoestrogens has also been demonstrated in vivo. For example, in mice, rats, and pigs, ZEN and metabolites readily bind uterine ERα and ERβ receptors [ 15 , 16 , 17 , 18 ]. Pig studies further suggest that zeranol has a higher affinity to ERα than ZEN or the metabolites α- and β-ZOL [ 17 ].…”
Section: Introductionmentioning
confidence: 99%